EMPOWERMENT OF CADRES IN INCREASING THE ROLE OF PARENTS FOR NUTRITIONAL FULFILLMENT AS AN EFFORT TO PREVENT STUNTING IN TODDLER - Bedho, Martina; Owa, Khrispina; Patmawati, Try Ayu (Fakultas Ilmu Kesehatan Universitas Borneo Tarakan, 2024)
The prevalence of stunting in Indonesia is among the highest compared to other countries in Southeast Asia, such as Myanmar at 35 percent, Vietnam 23 percent, and Thailand 16 percent. East Nusa Tenggara is one of the provinces in Indonesia that has a high prevalence of stunting. Gheoghoma Village, is a village supported by the Ende DIII Nursing Study Program which is located in North Ende District, Ende Regency. This village is outside the city of Ende, which means that educational information about children with stunting is less accepted by the community. Objective to increase knowledge and the role of parents in fulfilling nutrition as an effort to prevent stunting in toddler. In this activity the community service team provides health education for cadres and parents, training and mentoring. The results of the pre and post test measurements showed that in the pre stage the average knowledge of respondents was 45.91, while in the post stage it was found that the average student knowledge increased, namely 74.77 after being given material and training. Counseling has proven effective in increasing understanding of parents and cadres regarding stunting. Parents and cadres responded enthusiastically to the material because they gained new knowledge. Therefore, it is necessary to increase socialization and training activities for parents and cadres. Based on the monitoring and evaluation that has been carried out by the implementation team, the recommendation for the follow-up plan proposed by the team is that similar activities must be carried out continuously in the context of health promotion for the elderly.